Crime Scars: Recessions and the Making of Career Criminals - Bell, Brian; Bindler, Anna; Machin, Stephen (The Review of Economics and Statistics, 2018)
Abstract Recessions lead to short-term job loss, lower happiness, and decreasing income levels. There is growing evidence that workers who first join the labor market during economic downturns suffer from poor job matches that can have sustained detrimental effects on wages and career progressions. This paper uses U.S. and U.K. data to document a more disturbing long-run effect of recessions: young people who leave school during recessions are significantly more likely to lead a life of crime than those entering a buoyant labor market. Thus, crime scars resulting from higher entry-level unemployment rates prove to be long lasting and substantial.